Metabolic impact of feeding prior to a 60-min bout of moderate-intensity exercise in females in a fasted state - Ratliff, Kayla M.; Kerksick, Chad M.; Moon, Jessica M.; Hagele, Anthony M.; Boring, Johnathan L.; Walden, Kylie; Gaige, Connor J.; Stecker, Richard A.; Sunderland, Kyle L.; Mumford, Petey W. (Frontiers in Sports and Active Living, 2023)
Background: The metabolic impact of pre-exercise feeding of protein or carbohydrate on fat oxidation and energy expenditure rates, especially, in females, is poorly understood. Methods: Recreationally active females (n=15, 32 ± 10 years, 164.8 ± 5.6 cm, 63.5 ± 9.3 kg, 23.4 ± 3.2 kg/m2) completed four testing sessions in a randomized, double-blind, crossover fashion after fasting overnight. Participants ingested isovolumetric and isoenergetic solutions containing either 25g of whey protein, casein protein, carbohydrate (CHO), or a non-caloric placebo (PLA). Participants then completed 60 minutes of treadmill exercise at 15% below ventilatory threshold 30 minutes after ingestion. Substrate oxidation was evaluated throughout exercise and resting energy expenditure (REE) was assessed pre-exercise, and 0-, 60-, and 120-minutes post-exercise. Results: A significant condition x time interaction was observed for substrate oxidation (p = 0.008) during exercise, with CHO being higher than PLA at four time points. A significant main effect for condition was observed for oxidation rates of CHO (p = 0.12) and fat (p=0.20) during exercise, with fat oxidation being higher in PLA. A significant condition x interaction was observed for total fat oxidation (p = 0.02), with PLA having significantly higher values compared to CHO. A significant condition x time interaction (p = 0.02) was found for both absolute and normalized REE, with casein and whey protein having significantly higher values than CHO immediately post-exercise. Conclusion: Consuming CHO, but not protein, prior to a 60-minute bout of moderate-intensity exercise in females results in higher total fat oxidation when fasted.